Montgomery Clift, Queer Star - Girelli, Elisabetta (Book collections on Project MUSE., 2013)
Strikingly beautiful and exceptionally talented, Montgomery Clift was at the peak of his fame in 1956 when a devastating car crash nearly destroyed his face. While this traumatic event robbed him of his heartthrob status and turned him into a somewhat disturbing, socially alienated character, the author argues that Clift had always combined on-screen erotic ambiguity with real-life sexual nonconformity. In this book, she maps the development of Clift's subversive image over the span of his entire career, approaching Clift as a queer signifier who defied normative cultural structures. From the sexually ambivalent "beautiful boy" of his early films, to the seemingly asexual, transgressive, and often distressed man of his last years, the author argues that Clift shows remarkable consistency as a star: his presence always challenges established notions of virility, sexuality, and bodily "normality." This book uses queer theory to assess Clift's disruptive legacy, engaging with key critical concepts such as the closet, performativity, queer shame, crip theory, and queer temporality